(untitled) (Statistics, Optimization & Information Computing, 2025)
This paper examines the relationship between global health spending, CO2 emissions, the population aged 65 and above, GDP per capita growth, and GDP growth, utilizing a gradient-boosting algorithm. The paper confirms that the population aged 65 and older significantly influences current health expenditures (at 93%), GDP per capita growth (at 3%), and GDP growth and CO2 emissions, each contributing 2%. Additionally, the paper demonstrates a strong positive relationship between current health expenditures, the population aged 65 and older, and CO2 emissions. Conversely, there is a negative relationship between current health expenditures and both GDP growth and GDP per capita growth. This suggests that the world is optimistic about the transition to clean energy, which could lead to a decline in diseases and potentially reallocate part of health spending to other economic areas.